Sun keep rising - Lee, Kristen R. (Crown, 2023)
At risk of losing her home, teen mom B'onca forges a risky plan to help pay the bills that, if she makes one wrong move, could cost her and her family everything. A story about a teen mom navigating income disparity and racial inequality, and defying challenges to protect those she loves.